Lecturer’s Feedback toward Students’ Willingness to Communicate in Tertiary EFL Classrooms Interaction during the COVID-19 Pandemic - Rahmatika, Laily (Journal of English Teaching and Learning Issues, 2021)
The transformation of education during the COVID-19 pandemic has significantly impacted English teaching (EFL). To facilitate the successful implementation of this transformation, lecturers provide feedback to correct the error and enhance the skills of students to communicate. This study aims: (1) investigate the types of lecturer’s feedback used in the tertiary EFL interaction classroom during the COVID-19 pandemic and (2) identify types of lecturer’s feedback effect on students’ willingness to communicate of the tertiary EFL interaction classroom during the COVID-19 pandemic. Drawing on a qualitative study, data were collected by observation, audio and video recording, and transcription within two online tertiary EFL classroom of the Department of English Education at Universitas Muhammadiyah Surakarta. The result indicates that types of lecturer’s feedback into evaluative, interactive, corrective, and motivational feedback. Evaluative, corrective, and motivational feedback are identified effect in enhancing skills on students’ willingness to communicate. The results offer implications for language lecturers to be aware that providing feedback affects students' willingness to communicate success or failure.